Land degradation is indicative: proxies of forest land degradation in Ghana - Peprah, K (Brawijaya University, 2015)
How is land degradation measured? The aim of the paper is to address this research question. At the premise, the paper states that land degradation as one of the truth claims of environmental science, is not directly monitored and detectable. Observers rely on indicators to know land degradation. The issues are illuminated by theoretical reference based on the notion of critical political ecology which tries to combine realist biophysical predictions and socio-political constructions.Â A methodology which mixes literature review, group discussion and field work produces a set of indicators of land degradation. Indigenous farmers used the indicators to spot land degradation in the forest ecosystem of Ghana. The results reveal physical indicators of ironpan formation in farms, uphill and downhill respective lost and gain of soil fertility, roots and building foundations exposed by soil erosion and river channels that do not carry running water even in the raining season. There are biological indicators of invasive species and termite infestations as well as socioeconomic indicators of poverty implicitly taken as indicators of land degradation. The paper concludes that land degradation includes multifaceted set of processes measured by variable and error-filled indicators operating at various spatial, temporal, economic and cultural scales.